A Review of Potential Public Health Impacts Associated With the Global Dairy Sector. (13th February 2020) - Grout, Leah; Baker, Michael G.; French, Nigel; Hales, Simon
Abstract: Strong demand for dairy products has led to a global increase in dairy production. In many parts of the world, dairy systems are undergoing rapid intensification. While increased production may contribute to food security, higher dairy stocking rates in some regions have resulted in increased pressure on natural resources with the potential to affect public health and wellbeing. The aim of this review was to identify and describe the potential health harms and benefits associated with dairy production and consumption. Electronic databases Medline, Embase, Scopus, Web of Science, PubMed, and Google Scholar were searched for published literature that investigated human health impacts of dairy production and consumption. Occupational hazards, environmental health impacts, ecosystem health impacts, foodborne hazards, and diet‐related chronic diseases were identified as potential public health hazards. Some impacts, notably climate change, extend beyond directly exposed populations. Dairy production and consumption are also associated with important health benefits through the provision of nutrients and economic opportunities. As the global dairy sector increases production, exposure to a range of hazards must be weighed with these benefits. The review of impacts presented here can provide an input into decision making about optimal levels of dairy production and consumption, local land use, and identification and management of specific hazards from this sector. Future research should consider multiple exposure routes, socioeconomic implications, and environmental factors, particularly in regions heavily dependent on dairy farming. Plain Language Summary: As global population has increased, there has been an increase in demand for dairy products. In order to meet demand, dairy production has increased, and in many areas dairy farming has intensified, with large increases in the numbers of dairy cattle on farms. Rapid changes in dairy production may affect public health and wellbeing in a variety of ways. However, to the authors' knowledge, no comprehensive reviews of the potential health impacts associated with the production and consumption of dairy have been published. This review was undertaken in an effort to provide an overview of the linkages between the global dairy sector and public health, outlining both health hazards and benefits associated with dairy production and consumption. Occupational hazards, environmental and ecosystem health impacts, foodborne hazards, and diet‐related harms and benefits were identified as important potential public health impacts. Benefits include economic opportunities and provision of nutritious food. This review can support important decisions about how much dairy production and consumption is appropriate for optimal health, whether or not land should be converted to dairy production instead of alternative uses, and which hazards from dairy production require careful management and further research. Key Points: Strong demand for dairy products has led to global growth in production through farmland expansion and more intensive farming practices Impacts include exposure to occupational, environmental, and foodborne hazards, and diet‐related harms The range of harms must be weighed with benefits to food security, nutrition, livelihoods, and economic opportunities